Parent Involvement Pada Anak Penghafal Al-Qur’an Di SDIT Muhammadiyah Al-Kautsar - Nafisah Ahmad; Isnanita Noviya Andriyani (Academic Journal of Psychology and Counseling, 2022)
Parental involvement affects all aspects of child development. Especially in the field of religion which is a role model for children's lives in the future. This study aims to determine the involvement of parents in children who memorize the Qur'an. This type of research uses qualitative methods and a case study approach. The sampling procedure was purposive sampling with data collection techniques in the form of observation interviews accompanied by children's memorization books and reports on learning outcomes. The informants were three parents of children who took part in the tahfiz program with an age range of 7-11 years and different types of parental occupations. The data analysis used is pattern matching, explanation making, and time series analysis. The results showed that the informants gave their involvement in the form of parent involvement, both psychologically and physically. Parents are involved in all children's lives from development to the child's environment. No form of coercion or obsession was found in the process of memorizing the Qur'an in children. Children are still allowed to play and get rights according to their growth and development.